Does revealing personality data affect prosocial behavior? - Michalis Drouvelis; Nikolaos Georgantzis (Center for Economic Studies and ifo Institute (CESifo), 2019)
Many modern organisations collect data on individuals' personality traits as part of their human resource selection processes. We test experimentally whether revealing information on personality data impacts on pro-social behaviour as measured in a one-shot modified dictator game and a public goods game. Our focus is on the personality trait of agreeableness which has been shown to be a significant determinant of pro-sociality. We provide new evidence that revealing personality information for disagreeable individuals has detrimental effects on their pro-social behaviour as compared to the baseline no-information benchmark. This is not the case, however, for agreeable individuals when they are matched with agreeable individuals. Agreeable individuals become less pro-social when matched with disagreeable individuals and are aware of this. Our results suggest that information cues about personality significantly affect economic behaviour and have implications for employees' personality assessments as part of standard hiring processes.
Keywords: C91; D70; H41; 330; personality; social preferences; inequity aversion; cooperation; laboratory experiment